COVID-19 effects in comorbidities and special populations. - SANJAY KUMAR, BHADADA; NEERAJ, MITTAL; O P, KATARE ([S.l.] : BENTHAM SCIENCE PUBLISHER, 2022)
Coronavirus disease 2019 (COVID-19) has affected millions of people across the world. Clinicians and scientists across the globe need all the information of this pandemic on one platform. Today, it is also necessary to find out the association of COVID-19 with various medical comorbidities, and its effect on vulnerable populations that require special medical attention. This information will be helpful for the management of COVID-19. COVID-19: Effects in Comorbidities and Special Populations is a concise and visual reference for information about this viral disease and its relationship with different medical conditions. The book provides comprehensive knowledge covering COVID-19 comorbidities (for example, CVD, Diabetes, etc.) and the incidence in specific groups (for example, children and the elderly). Key Features: 12 chapters covering several aspects of COVID-19 management, making this a perfect text book for virologists and medical students Focused and structured description of different effects of COVID-19 in specific patient groups Multiple tables and figures which summarizes and highlight important points Multiple choice questions for learners Detailed list of references, abbreviations and symbols This book is an essential reference for practicing and training virologists, pulmonologists, medical students and scientists working in research labs, pharmaceutical and biotechnology industries in connection with the control of COVID-19 infection.
COVID-19: Effects in Comorbidities and Special Populations
eBooks on EBSCOhost
Keywords: COVID-19 (Disease); Comorbidity; Older people -- Health and hygiene; COVID-19; COVID-19.; Comorbidité.; Personnes âgées -- Santé et hygiène.; MEDICAL / Infectious Diseases; Comorbidity; COVID-19 (Disease); Older people -- Health and hygiene